Exploring Self-Consciousness From Self- and Other-Image Recognition in the Mirror: Concepts and Evaluation - Keromnes, Gaëlle; Chokron, Sylvie; Celume, Macarena-Paz; Berthoz, Alain; Botbol, Michel; Canitano, Roberto; Du Boisgueheneuc, Foucaud; Jaafari, Nemat; Lavenne-Collot, Nathalie; Martin, Brice; Motillon, Tom; Thirioux, Bérangère; et al. (Frontiers in Psychology, 2019)
A historical review of the concepts of self-consciousness is presented, highlighting the important role of the (particularly, body perception but also body action), and the in the construction of self-consciousness. More precisely, body perception, especially intermodal sensory perception including kinesthetic perception, is involved in the construction of a sense of self allowing self-other differentiation. Furthermore, the , through very early social and emotional interactions, provides meaning to the infant's perception and contributes to the development of his/her symbolization capacities. This is a necessary condition for body image representation and awareness of a permanent self in a time-space continuum (invariant over time and space). Self-image recognition impairments in the mirror are also discussed regarding a comprehensive developmental theory of self-consciousness. Then, a neuropsychological and neurophysiological approach to self-consciousness reviews the role of complex brain activation/integration pathways and the mirror neuron system in self-consciousness. Finally, this article offers new perspectives on self-consciousness evaluation using a double mirror paradigm to study self- and other- image and body recognition.